From Prompts to Prototypes: Exploring ChatGPT in Collaborative Software Prototyping Education - Pires, Alexandre; Kleinpaul, Enzo; Campos, Lorenzo; Parizi, Rafael (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
Generative AI (GenAI) tools, such as ChatGPT, have the potential to accelerate software prototyping and enhance team collaboration by generating content, expanding ideation, and enabling faster feedback cycles. As prototyping is central to agile and user-centered design, helping teams validate ideas, refine requirements, and align solutions with user needs, GenAI may further amplify these benefits through iterative and collaborative support. However, how to effectively integrate GenAI into collaborative prototyping remains underexplored in Software Engineering (SE) education. This study explores how ChatGPT supports collaborative prototyping among student teams, focusing on interaction, organization, and decisionmaking. We conducted a case study with undergraduate teams using ChatGPT in project-based prototyping. Data were gathered through a questionnaire, prompt analysis, and observation. Team collaboration and prior experience influenced the use of ChatGPT. Jointly crafted prompts led to more relevant outputs, while simpler prompts resulted in reliance on generic responses. Students valued the tool for speeding up prototyping and ideation, despite challenges with prompt refinement and occasional misalignment. The study provides insights into the use of GenAI for prototyping in SE education, shedding light on its benefits and limitations for co-creation and team dynamics.